2021
DOI: 10.1007/s00394-021-02625-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with serum ferritin levels and iron excess: results from the EPIC-EurGast study

Abstract: Purpose: Excess iron is involved in the development of non-communicable diseases such as cancer, type 2 diabetes and cardiovascular conditions. We aimed to describe the prevalence of excess iron and its determinants in healthy European adults.Methods: Sociodemographic, lifestyle, iron status, dietary information, and HFE genotyping were obtained from controls from the nested case control study EPIC-EurGast study. High sensitivity C-reactive protein (hsCRP) was measured to address possible systemic inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…In our study, female T2DM patients were 0.16 times less likely to increase serum ferritin level as compared to males (AOR = 0.16, 95% CI (0.05-0.57), p = 0.004). Our nding was consistent with other studies which showed that being male could be a risk factor for iron overload [57,58]. This might be due to the nature of females that may lose iron during the menstrual period as the menstrual cycle affects the iron homeostasis pathway [59].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, female T2DM patients were 0.16 times less likely to increase serum ferritin level as compared to males (AOR = 0.16, 95% CI (0.05-0.57), p = 0.004). Our nding was consistent with other studies which showed that being male could be a risk factor for iron overload [57,58]. This might be due to the nature of females that may lose iron during the menstrual period as the menstrual cycle affects the iron homeostasis pathway [59].…”
Section: Discussionsupporting
confidence: 92%
“…No iron chelation therapy was identified as a significant risk factor of developing cognitive impairment, which is consistent with the finding of an increased risk of cognitive impairment in patients with iron overload status. Serum ferritin, however, does not correlate with cognitive functions in some studies [10, 18] since serum ferritin depended on several factors that might not be measured in the earlier reports such as body mass index, menopausal status, and intake of vitamin C, calcium, and alcohol [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…The normal iron content in adults is about 60 g/dl; however, iron overload has deleterious effects and is involved in the development of cancer, type 2 diabetes, and cardiovascular conditions (7) , and can affect the normal functioning of the innate and adaptive immune responses (8) , promote the generation of reactive oxygen species and cell oxidative stress (9) and brain iron accumulation causes neurodegenerative diseases (10) .…”
Section: Introductionmentioning
confidence: 99%